Modeling of working conditions and wear resistance of the vehicle's clutch shaft - Рудик, О.Ю.; Дитинюк, В.О.; Стебелецька, Н.М. (Problems of Tribology, 2019)
It is shown that the basic characteristics of the quality of transport-technological machines and their aggregates are reliability and wear resistance, which reflect the service properties of these objects. The specified characteristics are laid down at designing and manufacture of cars, are realized in operation and restored with the help of repair. In the work, the methodology of the relationship between theory and experiment is complemented by the principles of computer simulation. This procedure made it possible to comprehensively study the behavior of complex systems, both natural and to test theoretical hypotheses. The application for studying the stress-strain state of solids of SolidWorks solid-state parametric modeling system has made it possible to construct an exact model of the component and the method of finite elements to determine the operational parameters for specific operating conditions. Investigation of the coupling shaft using SolidWorks Simulation showed that in the case of the replacement of 45X steel to steel 20, a safety margin was sufficient at the expense of the cost of the material. Using CAD to strengthen the shaft coupling clutch installed optimal mode of its cementation. The experimental results obtained confirm the relevance of the research on using SolidWorks Simulation. It is established that in the case of replacement of the tempered steel 45Х on cement steel 20 for manufacturing of the coupling sleeve shaft increase the wear resistance will be 1,49 times.